Nonmulberry silk proteins: multipurpose ingredient in bio-functional assembly. (22nd September 2021) - Naskar, Deboki; Sapru, Sunaina; Ghosh, Ananta K; Reis, Rui L; Dey, Tuli; Kundu, Subhas C
Abstract: The emerging field of tissue engineering and regenerative medicines utilising artificial polymers is facing many problems. Despite having mechanical stability, non-toxicity and biodegradability, most of them lack cytocompatibility and biocompatibility. Natural polymers (such as collagen, hyaluronic acid, fibrin, fibroin, and others), including blends, are introduced to the field to solve some of the relevant issues. Another natural biopolymer: silkworm silk gained special attention primarily due to its specific biophysical, biochemical, and material properties, worldwide availability, and cost-effectiveness. Silk proteins, namely fibroin and sericin extracted from domesticated mulberry silkworm Bombyx mori, are studied extensively in the last few decades for tissue engineering. Wild nonmulberry silkworm species, originated from India and other parts of the world, also produce silk proteins with variations in their nature and properties. Among the nonmulberry silkworm species, Antheraea mylitta (Indian Tropical Tasar), A. assamensis/A. assama (Indian Muga), and Samia ricini/Philosamia ricini (Indian Eri), along with A. pernyi (Chinese temperate Oak Tasar/Tussah) and A. yamamai (Japanese Oak Tasar) exhibit inherent tripeptide motifs of arginyl glycyl aspartic acid in their fibroin amino acid sequences, which support their candidacy as the potential biomaterials. Similarly, sericin isolated from such wild species delivers unique properties and is used as anti-apoptotic and growth-inducing factors in regenerative medicines. Other characteristics such as biodegradability, biocompatibility, and non-inflammatory nature make it suitable for tissue engineering and regenerative medicine based applications. A diverse range of matrices, including but not limited to nano-micro scale structures, nanofibres, thin films, hydrogels, and porous scaffolds, are prepared from the silk proteins (fibroins and sericins) for biomedical and tissue engineering research. This review aims to represent the progress made in medical and non-medical applications in the last couple of years and depict the present status of the investigations on Indian nonmulberry silk-based matrices as a particular reference due to its remarkable potentiality of regeneration of different types of tissues. It also discusses the future perspective in tissue engineering and regenerative medicines in the context of developing cutting-edge techniques such as 3D printing/bioprinting, microfluidics, organ-on-a-chip, and other electronics, optical and thermal property-based applications.